In Vitro Study of the Effect of Breathing Pattern on Aerosol Delivery During High-Flow Nasal Therapy - Bennett, Gavin (Pulm Ther, 2019)
INTRODUCTION: The use of concurrent aerosol delivery during high-flow nasal therapy (HFNT) may be exploited to facilitate delivery of a variety of prescribed medications for inhalation. The study assessed the effect of tidal volume, breath rate, and inspiratory:expiratory (I:E) ratio on the quantity of aerosol captured at the level of the trachea during simulated HFNT. METHODS: Testing was completed according to a factorial statistical design of experiments (DOE) approach. Tracheal dose was characterized with a vibrating mesh nebulizer (Aerogen Solo, Aerogen Ltd) using simulated adult, small child, and infant HFNT models. Furthermore, aerosol delivery was evaluated across a range of adult patient profiles with clinically representative test setups. RESULTS: Aerosol delivery increased with a large tidal volume, a rapid breath rate, and a long inspiratory time. Tidal volume, breath rate, and I:E ratio each had a significant effect on tracheal dose across simulated adult, small child, and infant breathing. CONCLUSION: The main trends that were identified in the statistical DOE predicted aerosol delivery across adult patient breathing profiles, in terms of tidal volume, breath rate, and I:E ratio. Therefore, patients with distressed breathing profiles may be expected to receive a larger aerosol dose than those with normal breathing rates. FUNDING: Aerogen Limited.